THE EFFECT OF GUIDE NOTE TAKING INSTRUCTIONAL MODEL TOWARDS PHYSICS LEARNING OUTCOMES ON HARMONIOUS VIBRATIONS - Darmawan Harefa (JOSAR (Journal of Students Academic Research), 2019)
This study aimed to investigate the effect of Guide Note Taking instructional model on student learning outcomes. This study used a quantitative approach with a quasi-experimental method. This research was conducted at SMA Negeri 1 Fanayama. The sample of this study was class X-1 as an experimental class with 32 students and class X-2 as a control class with 34 students. The instrument used in this study was an essay test consisting of 5 questions referring to the indicators of physics learning outcome. The results revealed that the average learning outcomes in the experimental class was 81.41, and the average learning outcomes in the control class was 67.5. Meanwhile, the hypothesis test obtained tcount = 5.94 and ttable = 1.99. This shows that tcount> ttable, therefore Ha is accepted and Ho is rejected. Based on data analysis and hypothesis testing, it is concluded that Guide Note Taking instructional model affects students' cognitive learning outcomes since it makes students interested in obtaining information or mastering skills to complete the given tasks.